2016
DOI: 10.1371/journal.pbio.1002563
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Suppresses Age-Associated Memory Impairment by Preventing Adverse Increase of Presynaptic Active Zone Size and Release

Abstract: Memories are assumed to be formed by sets of synapses changing their structural or functional performance. The efficacy of forming new memories declines with advancing age, but the synaptic changes underlying age-induced memory impairment remain poorly understood. Recently, we found spermidine feeding to specifically suppress age-dependent impairments in forming olfactory memories, providing a mean to search for synaptic changes involved in age-dependent memory impairment. Here, we show that a specific synapti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 94 publications
22
117
0
Order By: Relevance
“…It has been confirmed that Spd inhibits cell senescence induced by neuroinflammation and oxidative stress in striatum 36 and protects against aging-induced synaptic senescence. 15,37,38 These previous findings offered a reasonable explanation for the results obtained in the present study. Furthermore, the present work demonstrated that Spd also overcame HG-induced neurotoxicity in HT-22 cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been confirmed that Spd inhibits cell senescence induced by neuroinflammation and oxidative stress in striatum 36 and protects against aging-induced synaptic senescence. 15,37,38 These previous findings offered a reasonable explanation for the results obtained in the present study. Furthermore, the present work demonstrated that Spd also overcame HG-induced neurotoxicity in HT-22 cells.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicated that Spd is able to suppress HG‐induced senescence in HT‐22 cells. It has been confirmed that Spd inhibits cell senescence induced by neuroinflammation and oxidative stress in striatum and protects against aging‐induced synaptic senescence . These previous findings offered a reasonable explanation for the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is in line with the view that age-associated synaptic alterations might be the consequence of adaptive processes due to neuronal plasticity that compensate for age-dependent cognitive impairments [50]. Indeed, work of Gupta et al (2016) [42] demonstrated that a drop in postsynaptic excitability drives an increase of presynaptic scaffolds. According to the authors, this increase of presynaptic scaffolds might lead to an increase of synaptic vesicle release, which has been shown to be age-dependent [42].…”
Section: Discussionsupporting
confidence: 77%
“…The association between high spermidine uptake and reduced mortality is independent from confounding factors including age, sex, body mass index, consumption of alcohol or aspirin, metabolic syndrome, diabetes, physical activity, and socioeconomic status, as well as conventional dietary scores distinguishing healthy from unhealthy eating. These results confirm our long-lasting suspicion that spermidine has broad health-improving effects [2][3][4][5][6][7][8][9], based on our observation that nutritional supplementation of this polyamine can extend the longevity of multiple model species, including yeast, nematodes, flies and mice [10][11][12]. Here, we explore the literature linking spermidine to reduced cancer risk.…”
supporting
confidence: 76%